The Implementation of the Contextual Teaching and Learning Approach in Fiqh Education to Instill Religious Moderation - Al Ayyubi, Ibnu Imam; Nurhikmah; Prayetno, Eko; Noerzanah, Firda; Susilo, Akhbar (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study employs a quantitative, ex post facto approach to analyze students’ fiqh learning outcomes by school background. The research was conducted in three different schools: SDIT Miftahul Ulum, SDIT Al-Qalam Kendari, and MIS Muhammadiyah Bontoboddia, involving third-grade students from Jakarta, Southeast Sulawesi, and South Sulawesi. The total sample consists of 69 students, selected using probability sampling with a cluster sampling technique. Data analysis was conducted using descriptive and inferential statistics with One-Way ANOVA. The Kolmogorov-Smirnov normality test indicated that the data were normally distributed. However, due to differences in variance between groups, Levene’s test indicated that the data were not homogeneous. The ANOVA results showed a significant difference in fiqh learning outcomes among the schools. A Post Hoc test using Games-Howell confirmed substantial differences between SDIT Miftahul Ulum and SDIT Al-Qalam Kendari, as well as between SDIT Al-Qalam Kendari and MIS Muhammadiyah Bontoboddia, but no significant difference between SDIT Miftahul Ulum and MIS Muhammadiyah Bontoboddia. These findings indicate that implementing the Contextual Teaching and Learning approach in Islamic studies lessons yields varying impacts across schools.